Análise da atividade dos sais de ferro e desferroxamina na maturação de biofilme de micobactérias de crescimento rápido - Wille, Daniele Fernanda (2022)
Fast-growing mycobacterial infections have been gradually described in recent years, mainly because they are associated with a wide range of clinical syndromes, ranging from mild diseases to more severe disorders, such as skin and soft tissue infections, cervical lymphadenitis, chronic and disseminated lung infections. The formation of biofilms by these microorganisms is a major concern for public health, due to their greater pathogenicity in humans and resistance to antimicrobials. Thus, there is a pressing need to study and develop alternative methods of treatment, based on a careful assessment of the development and characterization of biofilms. Several factors are involved in the process of biofilm formation, among these components the presence of iron stands out, important in biofilm maturation. In this context, the present work aims to analyze the action of ferrous sulfate and ferric citrate in the formation of biofilms of fast-growing mycobacteria, as well as the deferoxamine chelator. To carry out this study, the strains Mycobacterium fortuitum (ATCC 6841), Mycobacterium massiliense (ATCC 48898) and Mycobacterium abscessus (ATCC 19977) were used. Ferrous sulfate and ferric citrate were the salts used for the treatment of fast-growing mycobacterial strains, as well as the chelator deferoxamine. Biofilms were formed and treated by semi-quantitative macro-technique and quantified using crystal violet and reading performed in a spectrophotometer. The results showed that there was interference of iron salts and deferoxamine in the formation of biofilms of the strains tested, since the formation of biofilm was significantly inhibited in the condition of iron deprivation in contrast to the control, in addition, the isolated deferoxamine presented antibiofilm activity, mainly for M. abscessus and M. massiliense, and it was possible to elucidate the importance of iron for biofilm formation in fast-growing mycobacteria by analyzing the mechanism of the anti-biofilm formation activity of deferoxamine. However, this work comes to encourage further research, in order to explore in more detail, the activity of new and promising molecules with antibiofilm activity.